The Political Economy of Good Governance - Huang, Wei-Chiao; Sisay Asefa, 1950- (Book collections on Project MUSE., 2015)
A notable group of social scientists explore the political economy of good governance and how it relates to performance management, the influence of political parties, education and health issues in developing countries, the economic performance of transition economies, and the effects of climate on poverty.